Peer-to-peer com a utilização do SCTP para aplicativos de compartilhamento de arquivos - Carmo, Gustavo Salvadori Baptista do (2006)
Peer-to-peer networks provide an efficient way for sharing computer resources. The transport layer underlies these networks. On the Internet, TCP and UDP are the mostly used protocols in this layer. SCTP is another transport layer protocol: related to TCP and UDP, SCTP offers additional functionalities that makes it more suitable to certain kinds of applications. This work aims to show the viability of the use of SCTP as the transport layer protocol for peer-to-peer file sharing applications, using the peculiar functionalities of this protocol to satisfy the needs of these applications in a more efficient way.